RFWD2 Knockdown as a Blocker to Reverse the Oncogenic Role of TRIB2 in Lung Adenocarcinoma - Hao, Ruimin; Hu, Jinxia; Liu, Yuemei; Liang, Dongmin; Li, Yan-Mei; Wang, Ranran; Zhang, Shucui; Wang, Pingyu; Li, You-Jie; Xie, Shuyang (Frontiers in Oncology, 2021)
RFWD2, an E3 ubiquitin ligase, is overexpressed in numerous human cancers, including leukemia, lung cancer, breast cancer, renal cell carcinoma, and colorectal cancer. The roles of RFWD2 in cancer are related to the targeting of its substrates for ubiquitination and degradation. This study aimed to investigate the role of TRIB2 in relation to the regulation of protein degradation through RFWD2. inBio Discover™ results demonstrated that TRIB2 can perform its functions by interacting with RFWD2 or other factors. TRIB2 can interact with and regulate RFWD2, which further attends the proteasome-mediated degradation of the RFWD2 substrate p-IκB-α. TRIB2 co-localizes with RFWD2-related IκB-α to form a ternary complex and further affects the IκB-α degradation by regulating its phosphorylation. Specific domain analysis showed that TRIB2 may bind to RFWD2 via its C-terminus, whereas it binds to IκB via its pseudokinase domain. TRIB2 acts as an oncogene and promotes cancer cell proliferation and migration, whereas RFWD2 knockdown reversed the role of TRIB2 in promoting cancer cell growth and colony formation in vitro and in vivo. In summary, this study reveals that TRIB2 promotes the progression of cancer by affecting the proteasome-mediated degradation of proteins through the interaction with RFWD2.